Surface Chemistry and Adsorption Behavior of Methylene Blue on Functionalized Carbon Materials: A Comprehensive Study - Ulfa, Maria; Hanif, Rizki Fauzia; Sholeha, Novia Amalia (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
The increasing release of synthetic dyes, particularly methylene blue (MB), from textile effluents has become a major environmental andhealth concern, highlighting the urgent need for efficient remediation strategies. Adsorption remains one of the most effective techniques for dye removal due to its simplicity, low cost, and high efficiency. This review discusses the surface chemistry and adsorption behavior of MB on functionalized carbon-based materials, emphasizing how physicochemical characteristics, surface modifications, and functional groups influence adsorption capacity and selectivity. Recent progress in developing engineered carbonaceous adsorbents—such as activated carbon (AC), graphene derivatives, carbon nanotubes, and hybrid carbon composites—has significantly improved the removal performance of MB through enhanced structural and chemical interactions. The ACHC-KOM-1 carbon composite, for instance, exhibits remarkable photocatalytic-assisted adsorption, achieving complete MB degradation under optimized conditions. Surface functional groups and pore architecture are decisive factors governing adsorption efficiency. Oxygen-containing moieties, including carboxyl (–COOH) and hydroxyl (–OH), create active sites that facilitate electrostatic attraction and hydrogen bonding with cationic MB molecules. Nitrogen functionalities (–N), introduced via heteroatom doping, enhance electron-donating properties and π–π interactions between MB aromatic rings and the conjugated carbon framework, thereby strengthening molecular affinity. Pore dimensions further regulate accessibility and diffusion, with micropores (<2 nm) providing strong confinement and high adsorption energy, while mesopores (2–50 nm) promote rapid diffusion and prevent pore blockage. The synergistic combination of abundant surface functionalities and hierarchical porosity governs the overall adsorption capacity, kinetics, stability, and regeneration potential of carbon-based adsorbents for dye removal. The mechanistic framework presented here distinguishes biomass-derived and non-biomass carbon adsorbents, enabling rational design of high-performance materials. These findings offer practical optimization guidelines for industrial-scale methylene blue removal while supporting sustainable, circular-economy-aligned water purification technologies.